THE DIFFERENCE PATTERN OF SUCCESSION BETWEEN SECOND GENERATION AND THRID GENERATION FAMILY BUSINESS IN INDONESIA (A REVIEW OF THE MEDIUM-SIZE FAMILY BUSINESS) - utami, christina whidya (Review of Management and Entrepreneurship, 2019)
The purpose of this study is to find out whether there are differences on pattern of succession between the second and the third generation of family business in Indonesia. Research Design/ Methodology/ Approach: A cross sectional and comparative research design were used in this study, while the data survey was conducted to 41 respondents from the second-generation group and 48 respondents from the third-generation family business; the businesses has run for 5 to 50 years and were categorized as medium size family business. The study used multiple regression test via SPSS to test the hypothesis. Findings: In family business led by the second-generation successor, only personality system affects the family business succession. On the other hand, in family business led by the third-generation, personality, ownership, family, and management system variables affect the success of the family business; meanwhile, family system does not find to affect the family business succession. Research Limitation/ Implication: This study investigates pattern of succession in family business including personality system, ownership system, family system and management system. This study can suggest a solution in the regeneration process of a family business in order to maintain the continuity of the business. limitation: There are some biases found on family’s perspective of the assessment, and the study only focus on medium-size family business. Practical Implications: A right amount of focus on pattern of succession will help the second and the third generation of the family to manifest in business succession. Exploring the second and the third-generation perspectives in regard to succession pattern is the key to maintain the continuity of the family business. Originality/ value: This study offers a pattern of succession from various perspectives, including personal, ownership, family, and management, as well as the relationship to the long-term success of the family business.